Ethical and socially responsible investment : a reference guide for researchers - Broadhurst, Dominic (Resource guides to business information sources., 2003)
This new reference guide gives details of over 500 ethical and socially responsible information sources. It is aimed at information professionals providing business information services, whether in the private or public sector.